Modern condition of Brachycera orthoptera’s (Orthoptera, Caelifera) fauna of the South of Сentral Russian upland - A.V. Prisny (Кавказский энтомологический бюллетень, 2007)
For the south of Central Russian upland, in view of data for last 100 years, 47 species of Orthoptera Brachycera are resulted. Among them 4 kinds, which have disappeared here for the nearest 50 years, 1 kind living on border of region, 2 species noted at its external borders. Now the fauna of region includes 42 kinds, two of its for the first time marked here. Principal causes of negative dynamics of borders of areas Orthoptera Brachycera in the south of Central Russian upland are almost utter annihilation on a plain herb-feather-grass and festuca-feather-grass steppes, significant reduction of extent water-separate plain oak groves with destruction of pubescent complexes, and also destruction of harmed and “potentially harmful” kinds in first half XX centuries. Anthropogenous xerothermisation of region leads more likely to pauperization of fauna with increase in a share and number xeromesophilous forms in local communities, than to it steppification. At the same time, sharply expressed xerothermisation of ironore area KMA already has led to distribution here typical semidesertic species, and deducing from an agricultural turn of a part of an arable land, haymakings and pastures - to restoration of an area of a flying locust